Revisiting the monetary presentation of the euro area balance of payments - Carmen Picón Aguilar; Rodrigo Oliveira Soares; Ramón Adalid (European Central Bank (ECB), 2020)
We explain how the external counterpart of the euro area M3 can be analysed by using the euro area balance of payments (b.o.p.). This is possible because the net external assets of the monetary financial institutions (MFIs) are present in two statistical frameworks that follow similar conventions: the balance sheet items (BSI) of MFIs and the balance of payments statistics. The first step to including external flows in the monetary analysis is to understand the nature of the flows between resident money holders and the rest of the world. This is possible thanks to the monetary presentation of the b.o.p, which provides information on the nature of external transactions and therefore guidance on the persistence of the monetary signal stemming from external flows. Over the past five years, the increase in the euro area's external competitiveness has given rise to a sustained current account surplus that has consistently supported monetary inflows into the euro area. At the same time, portfolio transactions, which closely reflect financial and monetary policy conditions, have fluctuated significantly, increasing monetary inflows in the period from mid-2012 to mid-2014 and turning them into net outflows during the asset purchase programme (APP) period.
Keywords: E51; E52; F45; F41; F43; F32; F34; 330; balance sheet items; balance of payments; monetary financial institutions; net external assets; cross-border flows; monetary aggregates